Association Between Western-Style Dietary Exposures and Hypertension Among Adults: A Systematic Review - Nurfatmi, Rezki; Sochibahariani, Putri Demylia (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction: Hypertension is a major global public health issue, affecting over 1.28 billion adults worldwide, with increasing prevalence in both developed and developing countries. Western dietary patterns, characterized by high consumption of processed meats, ultra-processed foods, sugary beverages, and high-sodium items, alongside low intake of fruits, vegetables, and whole grains, have been linked to elevated blood pressure and cardiovascular risk. This systematic review sumkimzes the evidence on the association between Western food consumption (including ultra-processed and fast foods) and hypertension in adults, and discusses its implications for public health and future research. Methods: Following PRISMA 2020 guidelines, a literature search was conducted in PubMed, Scopus, and ScienceDirect using keywords such as "Adult," "Western diet," and "hypertension." Inclusion criteria encompassed original quantitative studies on adults (≥18 years). Quality was assessed using Joanna Briggs Institute tools for cross-sectional and cohort studies. Data extraction focused on study characteristics, exposures, outcomes, and findings, with narrative synthesis applied. Results: From 646 records, five studies (four cross-sectional, one prospective cohort) from Norway, Nigeria, the United States, Vietnam, and South Korea were included, all with low risk of bias (87.5-100% JBI scores). Western-style patterns were associated with increased hypertension risk, uncontrolled hypertension, and metabolic syndrome components. Protective factors included plant-based diets and higher vegetable intake. No significant link was found in one study for hypertension specifically, but overall trends showed dose-response relationships. Conclusion: Western food consumption consistently elevates hypertension risk in adults across diverse populations, underscoring the need for public health interventions like sodium reduction, food reformulation, and nutrition education to mitigate this global burden.